2015
DOI: 10.1016/j.plefa.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid (DHA) supplementation in pregnancy differentially modulates arachidonic acid and DHA status across FADS genotypes in pregnancy

Abstract: Some FADS alleles are associated with lower DHA and ARA status assessed by the relative amount of arachidonic acid (ARA) and docosahexaenoic acid (DHA) in plasma and red blood cell (RBC) phospholipids (PL). We determined two FADS single nucleotide polymorphisms (SNPs) in a cohort of pregnant women and examined the relationship of FADS1rs174533 and FADS2rs174575 to DHA and ARA status before and after supplementation with 600 mg per day of DHA. The 205 pregnant women studied were randomly assigned to placebo (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…It could also be hypothesized that the reason for a lack of genetic influence on DHA status shown in the current study may be related to high fish consumption and subsequently higher levels of preformed DHA in the population, which may mean lower dependence on the endogenous synthesis pathway. This hypothesis is supported by the recent study by Scholtz et al where the influence of FADS genotype on DHA status became non-significant following fish oil supplementation among a group who had lower DHA status at baseline [ 37 ]. However, despite high fish intake in our cohorts, some endogenous activity for production of n-3 LC-PUFA might exist and thereby account for the higher LA:AA found in both cohorts and higher ALA:DHA found in NC2.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It could also be hypothesized that the reason for a lack of genetic influence on DHA status shown in the current study may be related to high fish consumption and subsequently higher levels of preformed DHA in the population, which may mean lower dependence on the endogenous synthesis pathway. This hypothesis is supported by the recent study by Scholtz et al where the influence of FADS genotype on DHA status became non-significant following fish oil supplementation among a group who had lower DHA status at baseline [ 37 ]. However, despite high fish intake in our cohorts, some endogenous activity for production of n-3 LC-PUFA might exist and thereby account for the higher LA:AA found in both cohorts and higher ALA:DHA found in NC2.…”
Section: Discussionmentioning
confidence: 65%
“…With respect to dietary variation, it is not fully understood how dietary availability of LC-PUFA impacts on the association between FADS genotype and LC-PUFA status [ 14 ]. It has been suggested that FADS genotype may be a greater determinant of LC-PUFA status in populations where fish consumption is low and there is expected to be greater dependence on endogenous synthesis of LC-PUFA [ 37 ]. Yet there remain no data on the influence of FADS genotype, on either LC-PUFA status or neurodevelopment, in populations with high fish consumption.…”
Section: Introductionmentioning
confidence: 99%
“…On average, ARA comprises 0.47±0.13% of total fatty acids in human milk [87]. The concentration of ARA in human milk varies between individuals and populations due, at least in part, to the presence of polymorphisms in the genes involved in the endogenous synthesis of LC-PUFAs [88].…”
Section: Structure Biological Sources and Functionsmentioning
confidence: 99%
“…A genetic variation in the FADS gene is linked to lower expression and activity of D5D and D6D, thereby increasing concentrations of the precursors linoleic acid (LA) and ALA but not of their downstream fatty acids AA, EPA and DHA [ 24 , 25 , 26 ]. The impact of dietary intakes and its potential to attenuate differences between major and minor allele carriers of the FADS polymorphism remains unclear [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%